2013
DOI: 10.1111/1556-4029.12298
|View full text |Cite
|
Sign up to set email alerts
|

The Discrimination of Colored Acrylic, Cotton, and Wool Textile Fibers Using Micro‐Raman Spectroscopy. Part 1: In situ Detection and Characterization of Dyes

Abstract: Raman spectroscopy has been applied to characterize fiber dyes and determine the discriminating ability of the method. Black, blue, and red acrylic, cotton, and wool samples were analyzed. Four excitation sources were used to obtain complementary responses in the case of fluorescent samples. Fibers that did not provide informative spectra using a given laser were usually detected using another wavelength. For any colored acrylic, the 633-nm laser did not provide Raman information. The 514-nm laser provided the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 21 publications
(30 reference statements)
0
28
0
Order By: Relevance
“…Similarly, an important two‐part study used Raman spectroscopy in situ for characterization and differentiation of acrylic, cotton, and wool fibers that were black, blue, or red in color. They demonstrated that the ability to obtain viable spectra significantly depended upon the laser wavelength used for analysis as well as the color and type of fiber . The second portion of this two‐part survey compared the results of analyzing 180 black, blue, and red cotton, wool, and acrylic fibers using Raman microspectroscopy with traditional methods including light microscopy, TLC, and UV–vis MSP .…”
Section: Trace Evidencementioning
confidence: 99%
“…Similarly, an important two‐part study used Raman spectroscopy in situ for characterization and differentiation of acrylic, cotton, and wool fibers that were black, blue, or red in color. They demonstrated that the ability to obtain viable spectra significantly depended upon the laser wavelength used for analysis as well as the color and type of fiber . The second portion of this two‐part survey compared the results of analyzing 180 black, blue, and red cotton, wool, and acrylic fibers using Raman microspectroscopy with traditional methods including light microscopy, TLC, and UV–vis MSP .…”
Section: Trace Evidencementioning
confidence: 99%
“…However, studies such as those published by Grieve et al [26], Palmer et al [11], Buzzini and Massonnet [10] and Massonnet et al [27], demonstrate that this may not be the case for all fibre type colour combinations (especially blue and black) cotton fibres.…”
Section: Discussionmentioning
confidence: 97%
“… Colour block studies: provide information on the ability of a scheme of analysis to discriminate between ostensibly similar fibres of a given generic fibre/ colour combination [6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, consideration of these minor peaks is critical in order to differentiate inkjet printer ink samples from different sources and also from the same manufacturer. This trait has not been noted for inkjet samples alone: Improvements in discriminations by consideration of the presence or absence of minor peaks have been previously achieved in the analyses of spray paints, blue gel pens, and dyed textile fibers …”
Section: Discussionmentioning
confidence: 99%
“…This trait has not been noted for inkjet samples alone: Improvements in discriminations by consideration of the presence or absence of minor peaks have been previously achieved in the analyses of spray paints, [23] blue gel pens, [24] and dyed textile fibers. [25] This important aspect has multiple implications. First, the discriminating capabilities of the method may be limited if differentiations only focus on the detection and identification of chemical compounds, because some dyes and pigments are more prevalent than others in inkjet formulations.…”
Section: Discussionmentioning
confidence: 99%